1970
DOI: 10.1172/jci106368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic potassium deficiency on plasma renin activity

Abstract: A B S T R A C T Serial determinations of plasma renin activity, sodium balance, urinary potassium excretion rate, and plasma sodium and potassium concentration were done in five dogs during dietary-induced potassium depletion and repletion. Duration of depletion for the different animals ranged from 5 to 7 wk.Plasma renin activity increased in all animals during depletion, with rises being demonstrated as early as the 1st depletion day in two of the dogs. Maximum values in the five dogs were recorded from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

1972
1972
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…This increase occurs independently of both the MD and of tissue K levels and is mediated by the renal vascular receptor. INTRODUCTION Chronic K deficiency results in an increase in plasma renin activity (1,2). Although the mechanism of the increase in renin activity has not been elucidated, it is known to occur independently of the changes in sodium balance that may accompany K depletion (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This increase occurs independently of both the MD and of tissue K levels and is mediated by the renal vascular receptor. INTRODUCTION Chronic K deficiency results in an increase in plasma renin activity (1,2). Although the mechanism of the increase in renin activity has not been elucidated, it is known to occur independently of the changes in sodium balance that may accompany K depletion (1,2).…”
mentioning
confidence: 99%
“…INTRODUCTION Chronic K deficiency results in an increase in plasma renin activity (1,2). Although the mechanism of the increase in renin activity has not been elucidated, it is known to occur independently of the changes in sodium balance that may accompany K depletion (1,2). There are, however, four alternative mechanisms whereby potassium depletion could influence the control ofrenin release (3).…”
mentioning
confidence: 99%
“…During the study with no sodium replacement the weight loss is perhaps commensurate with extracellular fluid loss and consistent with the rather elevated base-line renin values. During the second experiment the weight loss could not be correlated with the slightly positive sodium balance or the low base-line (6)(7)(8)(9)(10). In two of these studies (9)(10) an increase in aldosterone secretion rate has been shown, presumably due to the known effect of hyperkalemia or positive potassium balance on aldosterone (3,(14)(15)(16)(17)(18)(19) The PRA in our subjects responds appropriately to change in body sodium even during potassium loading.…”
Section: Resultsmentioning
confidence: 61%
“…Acute KCl infusions into the renal artery or systemic circulation have been shown to suppress renin secretion in both experimental animals and man (1)(2)(3)(4)(5)(6). Chronic potassium administration has also been shown to suppress renin values (7)(8)(9)(10). Since potassium loading stimulates aldosterone secretion, it is not clear whether the observed renin suppression is a direct potassium effect or is secondary to the rise in aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…in these rats has not been established. Since DI rats suffer from an absence of antidiuretic hormone (ADH) (Valtin & Schroeder, 1964) and potassium deficiency (Mohring et al 1974), and since both ADH (Bu-nag, Page & McCubbin, 1967; 520 E. FERNANDEZ-REPOLLET AND OTHERS Hesse & Nielsen, 1977;Vander, 1968;Vandongen, 1975) and potassium (Abbrecht & Vander, 1970;Dluhy, Underwood & Williams, 1970;Flamenbaum, Kleinman, McNeil, Hamburger & Kotchen, 1975;Sealey, Clark, Bull & Laragh, 1970;Vander, 1970) are known to exert an inhibitory effect on renin release, one or both of these factors might be involved in the elevation of p.r.a.…”
Section: Introductionmentioning
confidence: 99%